1999
DOI: 10.1212/wnl.53.3.605
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation identifies upper motor neuron involvement in motor neuron disease

Abstract: TMS provides a sensitive means for the assessment and monitoring of excitatory and inhibitory upper motor neuron function in motor neuron disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
1
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 32 publications
4
65
1
4
Order By: Relevance
“…One of our most striking findings is that TMS was more sensitive than clinical examination in patients with suspected or possible ALS, revealing UMN dysfunction in 75% (9 of 12) of the upper limbs. The sensitivity of CMCT in supporting the diagnosis reportedly increases with the number of muscles studied, 10,12,14,35,38,40,47 and this may apply to the parameters studied herein. We believe that, as for electromyography, several regions of the body, including muscles innervated by bulbar nerves, should be tested to increase the sensitivity of TMS in supporting a diagnosis of ALS.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…One of our most striking findings is that TMS was more sensitive than clinical examination in patients with suspected or possible ALS, revealing UMN dysfunction in 75% (9 of 12) of the upper limbs. The sensitivity of CMCT in supporting the diagnosis reportedly increases with the number of muscles studied, 10,12,14,35,38,40,47 and this may apply to the parameters studied herein. We believe that, as for electromyography, several regions of the body, including muscles innervated by bulbar nerves, should be tested to increase the sensitivity of TMS in supporting a diagnosis of ALS.…”
Section: Discussionmentioning
confidence: 58%
“…Transcranial magnetic stimulation (TMS) is a useful tool for diagnosing UMN dysfunction in ALS and provides a sensitive means of assessing cortical excitatory and inhibitory dysfunction. 10,12,14,35,38,40,47 The most frequently studied variables, which are generally recorded by conventional TMS using simple stimulation techniques, are central motor conduction time (CMCT), amplitude of motor evoked potentials (MEPs), resting motor threshold (RMT), and duration of silent period (SP). CMCT is reportedly not a sensitive variable for the diagnosis of ALS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that the silent period duration, which is a measure of the inhibitory response to TMS from many MUs, is shortened in ALS compared with normal control. 1,12,31,40 However, the silent period, which reflects both spinal and cortical inhibitory processes, is correlated with the size of the excitatory response. 2 The silent period decreases over time in relation to the loss of excitatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…По данным литературы, поражение верхнего мотонейрона обнаруживается не у всех пациентов с ПМА даже при использовании новейших методов исследования. Патоморфологиче-ски дегенерация пирамидного тракта выявляется в 50 % случаев [6], магнитно-резонансная спектроскопия выявляет поражение корковых мотонейронов у 60 % пациентов [7], нейрофизиологические методы (рутин-ная ТМС) -у 27-50 % [8,13,14]. Эти случаи ПМА яв-ляются, вероятно, вариантом БАС с субклиническим поражением верхнего мотонейрона.…”
Section: рис 2 карта коркового представительства правой M Abductorunclassified